1997
DOI: 10.1152/ajpregu.1997.273.6.r2089
|View full text |Cite
|
Sign up to set email alerts
|

Different modulation of steroidogenesis and prostaglandin production in frog ovary in vitro by ACE and ANG II

Abstract: Our aim was to study the role of angiotensin-converting enzyme (ACE) and angiotensin II (ANG II) on ovarian steroidogenesis and prostaglandin production of amphibian. Hormonal effects of ACE, ACE inhibitors, synthetic bullfrog angiotensin I (ANG I), and [Val5]ANG II were compared on frog ovaries of postreproductive and prereproductive periods. Very high ACE activity was found in ovary of water frog ( Rana esculenta) compared with other frog tissues, and this activity was inhibited by the typical ACE inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…1990; Howard and Husain 1992), rabbit (Brentjens et al. 1986) and frog (Bramucci et al. 1997) ovary.…”
Section: Introductionmentioning
confidence: 99%
“…1990; Howard and Husain 1992), rabbit (Brentjens et al. 1986) and frog (Bramucci et al. 1997) ovary.…”
Section: Introductionmentioning
confidence: 99%
“…ANG III, ANG-(1-7), and ANG- (3)(4)(5)(6)(7)(8) have some overlapping actions with ANG II because of partial occupancy of ANG II receptors, but importantly, ANG-(1-7) and ANG- (3)(4)(5)(6)(7)(8) have their own receptors that mediate opposing actions to ANG II (27,47). In the present study, HPLC analysis of luteal cell incubations showed peaks that eluted with the same retention times as ANG II, ANG III, and ANG-(1-7), and their relative quantities were ANG II Ն ANG-(1-7) Ͼ ANG III.…”
Section: Discussionmentioning
confidence: 99%
“…The substrate angiotensinogen is hydrolyzed by renin, releasing the decapeptide ANG I, which in turn is substrate for angiotensin-converting enzyme (ACE). ACE hydrolysis of ANG I results in the formation of the octapeptide ANG II, considered the major biologically active peptide of the cascade, and its proteolysis produces ANG III [ANG- (2)(3)(4)(5)(6)(7)(8)]. Historically, ANG II was considered an adrenal hormone restricted to renal function, but evidence that ANG II is produced by other tissues, including the ovaries, began to emerge in the 1980s.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We used an amphibian model to study the influence of ACE and Ang II on ovarian steroidogenesis and prostaglandin production. In the water frog Rana esculenta , 17 β ‐estradiol, progesterone, and prostaglandin E 2 (PGE 2 ) production was modulated by ovary ACE; on the other hand, Ang II modulated the production of progesterone and prostaglandin F 2 α (PGF 2 α ), whereas androgen production was not influenced (Bramucci et al . 1997).…”
mentioning
confidence: 99%